STRUKTUR MODAL DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN DENGAN CORPORATE SOCIAL RESPONSIBILITY (CSR) SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN MANUFAKTUR SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI PERIODE 2014-2017 - Ghonimah Zumroatun Ainiyah (Sekolah Tinggi Ilmu Ekonomi Tamansiswa Banjarnegara, 2019)
ABSTRACT The aim of this study was to determine the effect of capital structure and company size on firm value with Corporate Social Responsibility (CSR) an an intervening variable. The object examined in this study is a food and beverage sector manufacturing company listed on the Indonesia Stock Exchange for the period 2014- 2017. This type of research is quantitative research. The data used in this research is secondary data. The population in this study is the food and beverage sector manufacturing companies listed on the Indonesia Stock Exchange during 2014-2017 an many as 20 companies. The research sample was selected using a purposive sampling technique and obtained 13 companies. Data analysis in this study used a mediating variable regression analysis with a causal step method with SPSS 2016 software. The results of the study show the partially the capital structure has a negative and significant effect on firm value. Company size has a positive and not significant effect on firm value. Capital structure has a negative and not significant effect on CSR. Company size has a positive and significant effect on CSR. CSR has a positive and not significant. Effect on firm value. CSR cannot mediate the relationship between capital structure and firm value and between firm size and firm value.